Evaluation of Solar-Powered Battery Systems for Individuals Using Electricity-Dependent Medical Devices in Puerto Rico Following Hurricane Maria. (11th June 2023) - Tosado, Gabriella A.; Matos, Marvi; Ahumada-Paras, Mareldi; Chapko, Michael K.; Pozzo, Lilo D.
Abstract: Objectives: To determine if solar-powered battery systems could be successfully used for electricity-dependent medical devices by families during a power outage. Methods: We assessed the use of and satisfaction with solar-powered battery systems distributed to 15 families following Hurricane Maria in rural Puerto Rico. Interviews were conducted in July 2018, 3 mo following distribution of the systems. Results: The solar-powered battery systems powered refrigeration for medications and prescribed diets, asthma therapy, inflatable mattresses to prevent bedsores, and continuous positive airway pressure machines for sleep apnea. Despite some system problems, such as inadequate power, defective cables, and blown fuses, families successfully dealt with these issues with some outside help. Almost all families were pleased with the systems and a majority would recommend solar-powered battery systems to a neighbor. Conclusions: Families accepted and successfully used solar-powered battery systems to power medical devices. Solar-powered battery systems should be considered as alternatives to generators for power outages after hurricanes and other disasters. Additional research and analysis are needed to inform policy on increasing access to such systems.